Critical Illness–Associated Cerebral Microbleeds. Issue 4 (April 2017) - Fanou, Evgenia M.; Coutinho, Jonathan M.; Shannon, Patrick; Kiehl, Tim-Rasmus; Levi, Marcel M.; Wilcox, M. Elizabeth; Aviv, Richard I.; Mandell, Daniel M.
Abstract : Background and Purpose—: Cerebral microbleeds (petechial hemorrhages) are a well-known consequence of cerebral amyloid angiopathy and chronic hypertension among other causes. We report 12 patients with a clinically and radiologically distinct microbleed phenomenon in the cerebral white matter. Methods—: These patients were assessed at the University Health Network (Toronto, Canada) between 2004 and 2014. Results—: Median age was 40 years (range, 27–63 years), and 7 out of 12 patients were women. All patients had brain magnetic resonance imaging during or immediately after an intensive care unit admission. All patients had respiratory failure, 11 out of 12 received mechanical ventilation, and 3 out of 12 received extracorporeal life support. Magnetic resonance imaging in all 12 patients showed extensive microbleeds, diffusely involving the juxtacortical white matter and corpus callosum but sparing the cortex, deep and periventricular white matter, basal ganglia, and thalami. Several patients also had internal capsule or posterior fossa involvement. Conclusions—: We have described a distinct microbleed phenomenon in the cerebral white matter of patients with critical illness. The specific cause of the microbleeds is unclear, but the pathogenesis may involve hypoxemia as the microbleeds are similar to those described with high-altitude exposure. Abstract : Supplemental Digital Content is available in the text.